2016
DOI: 10.1007/s00705-016-2973-x
|View full text |Cite
|
Sign up to set email alerts
|

Bovine leukemia virus becomes established in dairy herds before the first lactation

Abstract: In this work, we studied seven groups of pregnant heifers from a consortium of dairy farms heavily infected with bovine leukemia virus (BLV). ELISA testing showed that the seroprevalence ranges of BLV in heifers between 36.1 and 66.5 %. No significant differences in proviral load were found when comparing heifers with adult cattle. Before their first delivery, more than 9.8 % of heifers show a high proviral load. Because BLV infection can occur during the first two years of life, the rationale of any strategy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Since high levels of BLV infection are associated with higher probability of transmission ( 69 ), the presence of animals with high PVL is epidemiologically dangerous. This could be a reason for the high incidence observed in Argentinean dairy herds before first parturition, when approximately half of pregnant heifers are already infected, and between 20 and 44% of them have high PVL ( 60 , 70 ). Culling the animals with high PVL might be a strategy for reducing overall incidence in the herds, but this would be economically feasible only in herds with low prevalence of high PVL cows.…”
Section: Importance Of Blv Infection During the Neonatal Periodmentioning
confidence: 99%
See 1 more Smart Citation
“…Since high levels of BLV infection are associated with higher probability of transmission ( 69 ), the presence of animals with high PVL is epidemiologically dangerous. This could be a reason for the high incidence observed in Argentinean dairy herds before first parturition, when approximately half of pregnant heifers are already infected, and between 20 and 44% of them have high PVL ( 60 , 70 ). Culling the animals with high PVL might be a strategy for reducing overall incidence in the herds, but this would be economically feasible only in herds with low prevalence of high PVL cows.…”
Section: Importance Of Blv Infection During the Neonatal Periodmentioning
confidence: 99%
“…However, it has also been reported that BLV infection can occur during the first 2 years of life, when young animals are still not in contact with adult cows. At this stage, the only potential sources of virus are their own mothers, bulk tank milk, and calves that were born infected (8–11% in dairy herds of Argentina) ( 60 , 70 ).…”
Section: Importance Of Blv Infection During the Neonatal Periodmentioning
confidence: 99%
“…Disease progression to B cell lymphoma is related to low expression of Tumor Necrosis Factor alpha (TNF-α), due to polymorphism in the promoter region 12 , and the animal’s Bola genotype 13 . The infection is considered eradicated in several parts of the world 14 but is widely spread in North 15,16 and most South American countries 17 including Brazil. As most retroviruses, transmission requires transferring of cells from infected to non-infected individuals 18 and, as such, blood and milk from infected animals are the main sources of the virus 19 .…”
Section: Introductionmentioning
confidence: 99%
“…A large percentile of animal infected by the BLV might be asymptomatic or aleukemic (AL), at least at the initial stages of infection, while up to 30% develop a persistent lymphocytosis (PL) 2 that in some cases, depending on the animal's Bola genotype, 3 progresses to B cell lymphoma 4, 5. The infection is considered eradicated in several parts of the world 6 but is widely spread in North7, 8, 9 and most South American countries 10 in which dairy farming is considered an important economic activity. There is no official data on the rate of infection in Brazilian dairy farm and most limited and biased epidemiological studies indicate that the range of seropositive animal varies from 12.5% to 100% 11, 12.…”
Section: Introductionmentioning
confidence: 99%